2019
DOI: 10.1007/s10336-019-01718-y
|View full text |Cite
|
Sign up to set email alerts
|

From plants to feces: pilot applications of FTIR spectroscopy for studies on the foraging ecology of an avian herbivore

Abstract: Studies on the foraging ecology of wildlife species are of fundamental importance, as foraging decisions are closely linked to ecological key issues such as resource partitioning or population dynamics. Using Black grouse as a model system, we applied Fourier-transform infrared spectroscopy (FTIRS) to address some key questions in foraging ecology: (1) does FTIRS allow for determining plant taxa and plant parts? Can FTIRS suggest variation in digestibility of food and physiological mechanisms of consumers? (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Foraging of animals is closely related to major ecological issues such as resource partitioning or population dynamics, thus studying foraging ecology of wildlife is important for wildlife management (Mayr et al 2020). Studies found that deer becomes more selective when supplemental feed is provided which improves their nutritional condition (Brown and Cooper 2006, Peterson and Messmer 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Foraging of animals is closely related to major ecological issues such as resource partitioning or population dynamics, thus studying foraging ecology of wildlife is important for wildlife management (Mayr et al 2020). Studies found that deer becomes more selective when supplemental feed is provided which improves their nutritional condition (Brown and Cooper 2006, Peterson and Messmer 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Nodes and, to a smaller degree, culms have a comparably sharp band in the fingerprint region ranging from 1580 to 1600 cm −1 . This could be assigned to asymmetric stretch vibration of carboxylates [15,16]. Even more likely, it could arise from the higher amount of lignin in nodes [17].…”
Section: Spectral Pattern Of Different Straw Partsmentioning
confidence: 99%
“…Chemical differences and changes can be assessed by this rapid and cost-efficient method. In wildlife biology, it has been introduced to study the nutrient concentration of solid rumen contents in moose [ 23 ] or diet quality of brown bear ( Ursus arctos ) [ 24 ], African elephants ( Loxodonta africana ) [ 25 ], and black grouse ( Tetrao tetrix ) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%